The effect of temperature of seed drying process on seed germination rate of chilli (capsicum frutescens l.) / Nor Haryati Mohammad Norzuki - Mohammad Norzuki, Nor Haryati (Faculty of Applied Sciences, 2014)
The objectives of the study was to determine the optimum temperature of seed drying process on seed germination rate of Capsicum frutescens L. and to compare the optimum temperature of seed drying process on seed germination rate between two types of Capsicum frutescens L. This study is about the preparation of the dried seed based on five different temperatures which are 28°C, 40°C, 60°C, 80°C and 100°C. The germination test were carried out in order to calculate its germination rate. The rate of germination represent as mean±standard deviation percentage. Results shows that the optimum temperature for the seed drying process on seed germination rate of Capsicum frutescens L. was at 40°C.The optimum temperature for seed drying process on seed germination rate of Capsicum frutescens L. (Type A) was at 40°C and for Capsicum frutescens L. (Type B) was at range 28°C to 60°C.